Practical Coupled Resonators in Domino Arrangements for Power Transmission and Distribution: Replacing Step-Down Power Transformers and Their Branches across the Power Grid. (18th July 2013) - Lazaropoulos, Athanasios G.
Abstract : This paper considers the potential of replacing step-down power transformers of the entire power grid as well as part of their transmission line branches with wireless power transfer (WPT) technology components. Exploiting the state-of-the-art evolutions in the fields of WPT technology, coupled resonators in domino arrangements—domino coupled resonator (DCR) configurations—are proposed as suitable technological substitute for step-down power transformers and are investigated in terms of performance metrics such as power transfer efficiency (PTE) and transformation ratio (TR). The contribution of this paper is fivefold. First, an analytical theoretical analysis appropriate to the study of practical DCR configurations is demonstrated. In order to support the DCR configuration replacement venture, a detailed set of assumptions regarding efficient mid- and long-range high-power WPTs as well as related technical issues is first presented. The validity of the theoretical analysis is verified through experimental measurements. Second, applying the proposed theoretical analysis, a wealth of system parameters that mainly influences the PTE and TR of DCR configurations is identified. Their quantitative effect as well as corresponding DCR configuration adjustments are first presented. Third, an approximate method, denoted as approximate chain scattering matrix (CSM) method, is first introduced. Based on the scattering matrix theory formalism, the approximate CSM method is suitable for mid- and long-range DCR configurations when the theoretical analysis becomes computationally slow. The numerical results of approximate CSM method are compared with the respective ones of theoretical analysis validating the extent and the accuracy of approximate CSM method. Fourth, the potential of power transformer replacement with practical DCR configurations is thoroughly investigated in terms of their TRs. A plethora of high-voltage/medium-voltage (HV/MV), MV/low-voltage (MV/LV), and HV/LV power transformers used across the world is investigated verifying their replacement potential with practical DCR configurations in all the cases examined. Fifth, based on a detailed collection of dimensions concerning power transformers and transmission line branches, it is first verified that practical DCR configurations cannot only substitute all step-down power transformers of the today's power grid but also replace entire transmission line branches too. Finally, it is obvious that there is a long journey ahead for WPT technology and its ultramodern DCR configurations to be affordably, widely, reliably, sustainably, and safely adopted in the human society. During these first steps of WPT development for power transmission and distribution, theoretical analyses and visions are necessary. The last cable problem, that is, the seamless power delivery as easily as information is now transmitted through the air, is one of the major technological challenges of the 21st century, and, thus, WPT technology will certainly play key role.